Assessement of the projection of the future changes in climate by RCP 2.6, RCP4.5, RCP8.5 - Basri, Abdul (2019)
The increase in global temperature give significantly impact on the climate changes. This situation will lead to the need for an assessment of regional climate change impacts. The application of Statistical Downscaling Model (SDSM) were used to simulate the projection of future climate trend in Melaka and Negeri Sembilan. The simulation was taken at three stations for each state which is Ranc. Tali Air, Ladang Sing Lian di Bhg Garing and Pintu Pasang Surut Duyong for Melaka, while JPS Tampin, Kg. Chennah and Politeknik Port Dickson for Negeri Sembilan. The SDSM model is the derivation of National Centre for Environmental Prediction (NCEP) reanalysis data and observation of locally methodological variables that have been calibrated using large – scale predictors variables. The SDSM model validation has been done by independent period of NCEP reanalysis. The result obtained was used to generate the future climate trend under various scenarios Representatives Concentration Pathways (RCP), RCP 2.6, RCP 4.5 and RCP 8.5 provided by the Canadian Centre for Climate Modelling and Analysis (CanESM2) at Melaka and Negeri Sembilan.